Evaluating of Existing VTE Risk Scales in Glioma Patients - Simakova Maria MD, PhD; Pishchulov Konstantin MD; Lukinov Vitaliy PhD; Voynov Nikita MD; Bulaeva Maria MD; Melnichnikova Olga MD, PhD; Zhilenkova Yulia MD, PhD; Savelyeva Аnna MD; Moiseeva Olga MD, PhD; Samochernykh Konstantin MD, PhD (Clinical and Applied Thrombosis/Hemostasis, 2024)
Introduction Postoperative venous thromboembolism (VTE) is a frequently occurring complication among glioma patients. Several risk assessment models (RAMs), including the Caprini RAM, the IMPROVE Risk Score, the IMPROVED VTE Risk Score, and the Padua Prediction Score, have not been validated within the glioma patient population. The purpose of this study was to assess the predictive accuracy of established VTE risk scales in patients with glioma. Materials and Methods A single-center, retrospective, observational cohort study was conducted on 265 glioma patients who underwent surgery at the Almazov Medical and Research Centre between 2021 and 2022. VTE detection followed the current clinical guidelines. Threshold values for the Caprini, IMPROVE VTE, IMPROVEDD, and Padua scales were determined using ROC analysis methods, with cumulative weighting for sensitivity and specificity in predicting VTE development. The areas under the ROC curves (AUC) were calculated, and comparisons were made using the DeLong test. Results The area under the curve for the Caprini risk assessment model was 80.41, while the IMPROVEDD VTE risk score was 75.38, the Padua prediction score was 76.9, and the IMPROVE risk score was 72.58. No significant differences were observed in the AUC values for any of the scales. The positive predictive values of all four scales were low, with values of 50 (28–72) for Caprini, 48 (28–69) for IMPROVEDD VTE, 50 (30–70) for Padua, and 64 (35–87) for IMPROVE RAM. No significant differences were found in terms of PPV, NPV, positive likelihood ratio, and negative likelihood ratio among the analyzed scales. Conclusions The Caprini Risk Assessment Model, the IMPROVE Risk Score, the IMPROVED VTE Risk Score, and the Padua Prediction Score exhibit acceptable specificity and sensitivity for glioma patients. However, their low positive predictive ability, coupled with the complexity of interpretation, limits their utility in neurosurgical practice.